EFEKTIFITAS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS IX-B SMP PATARUMAN - Nurul Khuzaimah; Anik Yuliani; M. Afrilianto (IKIP Siliwangi, 2023)
This study aims to examine the effectiveness of the scientific approach applied in geometry transformation material to improve the mathematical critical thinking skills of junior high school students. This research method uses classroom action research. The subjects of this study were students of class IX-B Pataruman Cihampelas junior high school with 12 male students and 8 female students, totaling 20 students. The stages of this research include; Planning, implementing actions, observing and evaluating, and reflecting. This stage is carried out repeatedly (cycles) until the desired student learning outcomes are achieved. In this study, there were 2 cycles. Where the first cycle is carried out online and the second cycle is carried out offline. To evaluate and measure student learning outcomes, test instruments are given in the form of description questions which are carried out before and after the action or often referred to as pretest and posttest. The results of this study indicate that the application of the scientific approach is considered effective to improve mathematical thinking skills in the material of geometric transformation in class IX-B of Pataruman junior high school.